Isolated Arthroscopic-Assisted Subtalar Fusion: A Systematic Review. Issue 8 (August 2021) - Loewen, Allison; Ge, Susan M.; Marwan, Yousef; Berry, Gregory K.
Abstract : Background: The subtalar joint has a complex anatomic function that includes inversion and eversion of the hindfoot, assisting in walking on uneven surfaces. Arthritis is the most common pathological condition affecting this joint and can require fusion. The surgery can be performed open or with arthroscopic assistance. This systematic review assesses articles written on the safety and efficacy of isolated arthroscopic subtalar fusion. Methods: Using MEDLINE and Embase, we systematically reviewed articles published before May 21, 2020. Results: Of 395 articles, 17 on a total of 395 patients (409 operations) were included in the review. The average duration of follow-up was 40.0 months (range, 3 to 105 months). Radiographic evidence of union was reported for 95.8% of cases at an average of 11.9 weeks (range, 6 to 56 weeks) postoperatively. Delayed union was reported in 1.0% of patients and nonunion, in 4.3% of patients. In the articles reporting patient satisfaction, including pain relief, 95.4% of patients had positive outcomes. Postoperative complications were reported in 64 patients (16.2%), including 37 (9.4%) with symptomatic implants, 11 (2.8%) with dysesthesia or neuropathic pain, and 3 (0.8%) with postoperative infection. Conclusions: Arthroscopic subtalar fusion is a safe and effective alternative to open subtalar arthrodesis, with high patient satisfaction rates, high union rates at similar follow-up intervals, and low complication rates. The aim of future research should be to determine the ideal cases for this approach as well as the most efficient arthroscopic surgical technique and postoperative rehabilitation to optimize function and union as seen on radiographs. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.